Constraints Perceived by Dealers and Households for Execution and Adoption of Pradhan Mantri Ujjwala Yojana - Bijaylaxmi Behera,; Biswajit Mallick, (Indian Journal of Extension Education, 2023)
Considering the perception of the LPG dealers and households towards Pradhan Mantri Ujjwala Yojana, the current study was carried out in the Samastipur district of Bihar in 2022. A total of 110 respondents i.e., 100 women households and 10 LPG dealers were taken for the study from 4 villages of 2 blocks under Samastipur district. 21 specific constraints perceived by households and 18 specific constraints perceived by dealers were categorized into 4 broad constraints, viz., social, cultural, economic, and physical constraints. Analysis was performed by using Garrett’s ranking method, and specific constraints were ranked accordingly. Garrett’s mean scores of specific constraints ranged 29.38 to 73.41 for social constraints, 30.15 to 69.03 for cultural constraints, 27.73 to 71.77 for economic constraints, and 29.50 to 70.60 for physical constraints as perceived by households. The mean score of constraints perceived by dealers were 30.4 to 71.3 for social constraints, 31.5 to 73.5 for cultural constraints, 26.5 to 70.5 for economic constraints, and 34.5 to 66.7 for physical constraints. The paper may  provides a better insight into the grassroots level constraints for implementation and acceptance of Pradhan Mantri Ujjwala Yojana in rural villages of India.